Acute traumatic unilateral cervical C4–C5 facet dislocation in pediatric toddlers - Liawrungrueang, Wongthawat (BMC Musculoskelet Disord, 2020)
BACKGROUND: The present study is to highlight the challenges in managing cervical spine injuries in toddlers (less than 4 years of age) without neurological deficit. Cases of unilateral cervical C4–C5 facet dislocation in toddlers are very rare. CASE PRESENTATION: A 3-year-old girl suffered cervical spine injury after a motor vehicle collision with unilateral C4–C5 facet dislocation without neurological deficit. Magnetic resonance imaging (MRI) showed no spinal cord injury, Frankel grade E. Initial management was cervical spine protection. Definite treatment and complication were discussed with the patient’s parents before closed reduction maneuver with minerva cast was applied under sedation. The patient showed no complication after closed reduction and the cervical spine had aligned well in radiographs. The minerva cast was removed at 8 weeks, at which point neck muscle stretching rehabilitation program started. At one-year follow up, the child was asymptomatic, had full active cervical motion and good function. In radiographs, the cervical spine had normal alignment and was healed. CONCLUSIONS: Unilateral cervical facet dislocation in toddlers is very rare. Closed reduction maneuver and the minerva cast applied were optional in this case. The parents were highly satisfied with the effective treatment and outcome.